Derechos lgbtiq+ en estados unidos: la narrativa de la corte suprema de justicia en materia de igualdad y no discriminación - Almejun, Juan Martin (2020)
In this paper, we will focus on transcribing and translating the facts and arguments that sustain the cases Masterpiece Cakeshop v. Colorado Civil Rights Commission and Bostock v. Clayton County, Georgia to provide some reflections on the narrative of the United States Supreme Court and their impact in the LGBTIQ+ rights. Also, we will analyze the consequences of the sentences and what they represent for the movement?s struggle. Besides, we will see the changes in the Court narrative in each sentence and we will compare them. Finally, the current and future political and legal opportunities in this subject will be briefly examined